“Gehörnte Mutter Hirschkuh” (Anacr. F 408 PMG) in der antiken philologischen Polemik - Pozdnev, Michael (Hyperboreus, 2016)
The “horned doe” exempliﬁes in Aristotle’s Poetics c. XXV the kind of errors κατ’ ἄλλο συμβεβηκός, i. e. the unconscious errors against reality that poets are sometimes vulnerable to. It appears again in the learned polemic led by Aristophanes of Byzantium against Zenodotus: the argument and the examples given are reproduced by Aelian and in the scholia on Pindar. Zenodotus emended κεροέσσης (μητρός) in the text of Anacreon suggesting to read ἐροέσσης. This Aristophanes tried to refute showing that the ancient poets never hesitate to represent doe with horns. I. Bywater (to cite only the ﬁrst of the many prominent commentators on the Poetics of the last century) and W. Slater (commenting on Aristophanes) make the same assertion. However, by examining all or at least the majority of the extant representations of this kind in ancient Greek poetry and art (there are also parallels in the Kirgiz folklore) we come to the conclusion that the animals they deal with are virtually different from that shown by Anacreon. Those are mostly if not entirely fabulous, and intentionally portrayed as such (as it was stated already by Timotheus of Gaza ca. AD 500), whereas the Anacreontean “horned mother” only paraphrases the “doe”: Horace’s imitation of the poem (Carm. 1, 23) shows well enough that there is no need to suppose any mythic context. The example could have been marked as speciﬁc by Aristotle as well as by Zenodotus whose decision to alter the text was thus better motivated than the objections made by Aristophanes. The only objection against his conjecture (which, however, has never been made) is provided by the semantics: ἐρόεις can hardly be attributed to μήτηρ. Anacreon made an unconscious mistake, which is not a singular case even among the great classics. Supposedly Aristotle discussed just that class of mistakes and based his discussion primarily on that example. Still, the Alexandrians were unaware of his views, for neither of them doubted that poetry should provide evidence of things that really occur in nature, and the permissibility in poetry of things impossible in reality was never put in question.